The Values of Nighttime in Classical Antiquity : Between Dusk and Dawn - Ker, James; Wessels, Antje (Mnemosyne, Supplements, 2020)
In ancient Greece and Rome, nighttime encompassed a distinctive array of cultural values that went far beyond the inversion of daytime. Night was a mythological figure, a locus of specialized knowledge, a socially significant semantic space in various literary genres, and a setting for unique experiences. These facets of night are explored here through fifteen case-studies, that range from Hesiod to imperial Roman painting and cultural history. The contributors took part in a conference on this theme at the University of Pennsylvania in 2018, where they pursued a common goal: to consider how nighttime was employed in the ascription of specific values-in determining what values a thing or a person might have, or lack, in a nocturnal context.